Modern Strategies in Cancer Study: Drug Repositioning in Colorectal Cancer Treatment - Anselmino Dieterle, Luciano Emanuel (2019)
Colorectal cancer is one of the most fatal cancers in the world because most of cases are diagnosed in advanced stages, when the development of resistance to chemotherapy is more frequent. To face this situation, new drugs and drug combinations would be necessary. Drug discovery is a very costly process; although efforts in drug discovery have been amplified in recent decades the success rate of approved FDA drugs continues being low. In response to this situation the repositioning of drugs proposes to delve into the genetic, epigenetic and metabolic differences to discover new targets and redirect drugs already approved to the treatment of other diseases and conditions. In this minireview we discuss the main avenues in which repositioning can occur and we cite some examples of repositioning drugs in colorectal cancer treatment that are being tested in clinical trials in the last years.